The implementation of formative assessment policies in two Grade 10 life science classrooms in the Keetmanshoop district - Van Neel, Adrian Richerd (Rhodes University, Faculty of Education, Department of Education, 2007)
This research project investigates the implementation of formative assessment policies in the Life Science curriculum at two schools in the Keetmanshoop District, Karas Education Region. It takes the form of an interpretive case study and adopts a qualitative approach. Several data collection tools were used: classroom observation, document analysis and semi-structured interviews. Two of the eleven schools in the Karas Region offering Grade 10 Life Science were selected for the study, and the research participants at each school consisted of one Grade 10 Life Science teacher and five of their learners. The study situates itself in the context of Namibian educational reform by reviewing relevant literature pertaining to learner-centred (constructivist) education and assessment practices in pre- and post-independent Namibia. The study highlights issues pertaining to formative assessment that are at variance with reform policies, identifying six recurring themes that explain how formative assessment policies are implemented. These are teachers' perceptions of formative assessment and its role in teaching and learning, the type of learning being developed, marking/assessing assessment tasks, the integration of formative assessment into classroom instruction, strategies teachers used to implement formative assessment, and types and purpose of activities. The themes that evolved during the data gathering process provide insight into the ways in which teachers perceive formative assessment in relation to the ideals of Namibian educational reform policies. In the light of these findings, the study makes recommendations concerning the implementation of formative assessment policies so as to render these congruent with the theory underpinning leamer-centred education.
Keywords: Life sciences -- Study and teaching -- Namibia; Education -- Namibia; Educational change -- Namibia